The causes of corruption: evidence from China - Bin Dong; Benno Torgler (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this study we explore in detail the causes of corruption in China using two different sets of data at the regional level (provinces and cities). We observe that regions with more anti-corruption efforts, histories of British rule, higher openness, more access to media and relatively higher wages of government employees are markedly less corrupt; while social heterogeneity, regulation, abundance of resource and state-owned enterprises substantially breed regional corruption. Moreover, fiscal decentralization is discovered to depress corruption significantly, while administrative decentralization fosters local corruption. We also find that there is currently a positive relationship between corruption and economic development in China that is mainly driven by the transition to a market economy.
Keywords: D73; H11; K42; 330; Corruption; China; Government; Decentralization; Deterrence; Social Heterogeneity